Mucormycosis: A comparative update between conventional and molecular diagnosis strategies - Shikha Moudgal; Shalinee Rao; Manju Pai (Mazandaran University of Medical Sciences, 2022)
Mucormycosis is an opportunistic, aggressive, and angioinvasive fungal infection associated with a high mortality rate as it disseminates and infects the whole body if not treated early. Most conventional diagnostic methods require time and may also generate false-negative reports due to the several lacunae associated. On the other hand, molecular methods are rapid, reliable, and can be applied to different biological samples, such as fresh tissue, formalin-fixed paraffin-embedded blocks, serum, and urine. Mucorales are angio-invasive, and many studies have found the circulating fungal DNA (a non-invasive form of DNA) in the blood and urine of the patient. In addition, with the increase in the usage of steroid drugs in this COVID scenario, the rate of mucormycosis infection has taken a sudden rise. In light of this situation, there is an imperative need to diagnose these infections at the earliest.Studies on the diagnosis of mucormycosis were explored and retrieved from Pubmed and Google Scholar. Histopathology and culture reports of patients diagnosed with mucormycosis in 2019-2020 were searched and retrieved from the hospital database (ethically permitted) to find the rate of concordance between the techniques.In this review study, different tested molecular techniques are encapsulated, and various primers are documented that are used to identify and classify different Mucoromycota fungi.An attempt has been made to compare the feasibility, accuracy adaptability, and time frame used among molecular and conventional methods for the diagnosis of mucormycosis.